ANALISIS PENGARUH INVESTASI, TINGKAT UPAH, DAN TINGKAT PENDIDIKAN TERHADAP PENYERAPAN TENAGA KERJA DI PROVINSI SUMATERA BARAT (PERIODE TAHUN 1994-2023) - Mhd. Taufik Hidayat; Amsah Hendri Doni (CV. ADIBA AISHA AMIRA, 2024)
This study aims to analyze the effect of investment, wage level, and education level on labor absorption in West Sumatra Province. The data used in this study are secondary data obtained from the West Sumatra Central Bureau of Statistics during the period 1994- 2023. Data collection techniques using literature study and documentation. The analysis method used in this study is the Classical Assumption Test which includes the Autocorrelation Test, Multicollinearity Test, Normality Test, and Heteroscedasticity Test, Multiple Linear Regression Analysis Test, Determination Coefficient (R-Square) test, Hypothesis t test and Hypothesis f test. The results show that investment (X1) has no significant effect on labor absorption, while the level of wages (X2) and the level of education (X3) have a positive and significant effect on labor absorption. The R-Square value is 0.937 (93.7%) while the remaining 0.063 (6.3%) is influenced by other independent variables not included in this study such as the value of production